Visualization of the entire process of rice spikelet infection by Ustilaginoidea virens through nondestructive inoculation - Hu, Xianfeng; Wang, Jian; Zhang, Yubo; Wu, Xiaomao; Li, Rongyu; Li, Ming (Frontiers in Microbiology, 2023)
Introduction Rice false smut caused by Ustilaginoidea virens, is a destructive fungal disease encountered in many rice-producing areas worldwide. To determine the process by which U. virens infects rice spikelets in the field. Methods The green fluorescent protein-labeled U. virens was used as an inoculum to conduct artificial inoculation on rice at the booting stage via non-destructive panicle sheath instillation inoculation. Results The results showed that the conidia of U. virens germinated on the surface of rice glumes and produced hyphae, which clustered at the mouth of rice glumes and entered the glumes through the gap between the palea and lemma. The conidia of U. virens colonized in rice floral organs, which led to pollen abortion of rice. U. virens wrapped the whole rice floral organ, and the floral organ-hyphae complex gradually expanded to open the glumes to form a rice false smut ball, which was two to three times larger than that observed in normal rice. Discussion Panicle sheath instillation inoculation was shown to be a non-destructive inoculation method that could simulate the natural infection of U. virens in the field. The entire infection process of U. virens was visualized, providing a theoretical reference for formulating strategies to control rice false smut in the field.